Evaluation of yield and forage quality in main and ratoon crops of different sorghum lines - Vinutha, K.S.; Anil Kumar, G.S.; Blümmel, Michael; Srinivasa Rao, P. (International Center for Tropical Agriculture, 2017)
Improving the yield and quality of sorghum (Sorghum bicolor) forage for livestock feeding is a major breeding objective, because of sorghum’s inherently high biomass accumulation, high productivity per unit water utilized and its ability to produce a ratoon crop after harvesting of the plant crop. Newly bred sorghum lines, including 36 lines falling in 5 different categories, i.e. 12 experimental dual-purpose lines, 6 germplasm accessions from the ICRISAT collection, 11 commercial varieties and hybrids, 6 forage varieties and 1 bmr mutant line, were evaluated in terms of fodder yield, quality and ratooning ability. The main crop produced more dry biomass (P<0.05) at 80 days after planting (mean 22.87 t DM/ha; range 17.32‒33.82 t DM/ha) than the ratoon crop (mean 8.47 t DM/ha; range 3.2‒17.42 t DM/ha) after a further 80 days of growth. Mean nitrogen concentration in forage did not differ greatly between main and ratoon crops (2.56 vs. 2.40%, respectively) but there was wide variation between lines (2.06‒2.89%). The line N 610 recorded highest N percentage of 2.89%, followed by SSG 59 3 (2.86%) and SX 17 (2.81%). Highest acid detergent fiber % was recorded by ICSV 12008 (42.1%), closely followed by CO 31 and IS 34638 (40.0%). The least acid detergent lignin % was observed in MLSH-296 Gold (3.59%), ICSV 700 (3.75%) and ICSSH 28 (3.83%). Metabolizable energy concentration was highest in N 610, Phule Yashodha and SX 17 (mean 8.34 MJ/kgDM), while in vitro organic matter digestibility ranged from 52.5 to 62.6%. The main crop contained much higher mean concentrations of the cyanogenic glycoside, dhurrin, than the ratoon (639 vs. 233 ppm, respectively) with ranges of 38 to 2,298 ppm and 7 to 767 ppm, respectively. There was no significant correlation between dhurrin concentration and dry biomass yield so breeding and selection for low dhurrin concentrations should not jeopardize yields. Hence, breeding for sorghum can target simultaneously both quality and biomass improvement.